Boron Removal from Silicon Using Secondary Refining Techniques by Metallurgical Method. Issue 1 (2nd January 2020) - Wu, Jijun; Yang, Ding; Xu, Min; Ma, Wenhui; Zhou, Qiang; Xia, Zhenfei; Lei, Yun; Wei, Kuixian; Li, Shaoyuan; Chen, Zhenjie; Xie, Keqiang
Abstract : Impurity removal, the purification process from metallurgical grade silicon (MG-Si) required to obtain solar grade silicon (SoG-Si), is crucial to the preparation of silicon-based solar cells. Some processes for boron removal by metallurgical method were reviewed. Secondary refining techniques, including gas blowing, slag treatment, plasma refining, solvent refining and other refining silicon techniques were summarized. The effects of gas species and slag systems on boron removal efficiency were emphatically discussed. Experimental and theoretical investigations show that a united technique of combining water vapor and oxygen gases blowing with slag treatment containing chloride or fluoride has achieved an amazing improvement for boron removal from molten silicon. Plasma refining and solvent refining also display high efficiency but acid leaching treatments, vacuum volatilization, electron beam and directional solidifications are hardly effective to boron removal. As for the potential industrial application of this united technique, the authors propose that some experimental and theoretical studies in dynamics should be further explored.